Women in mining: an ethnographic study of heavy equipment operators in Indonesian coal industry - Siswanto, Agus; Heikal, Jerry (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This research investigates the factors motivating women to work in the traditionally male-dominated mining industry, focusing on heavy equipment operators at a coal mine in Sangatta, East Kalimantan, Indonesia. Employing an ethnographic approach with a phenomenological study design, data were collected through in-depth interviews with three informants with varying lengths of work experience to identify shared values. The findings reveal three primary factors underpinning women's decisions to pursue mining careers: strong work ethic, economic motivations, and an orientation towards self-development and securing their children's future. These findings demonstrate women's agency in career decision-making and their ability to transcend gender stereotypes. This study recommends that mining companies foster inclusive work environments that support women in balancing their multiple roles.